Common mistakes at IELTS advanced--and how to avoid them - Moore, Julie (Cambridge books for Cambridge exams, 2007)
This invaluable little book highlights the real mistakes that students make in the exam - and shows how to avoid them. Based on analysis of thousands of exam scripts, each unit targets a key problem area. Clear explanations and exercises help students to use the language accurately. Regular tests offer students a further opportunity to check and consolidate what they have learnt. • Highlights common mistakes that learners really make. • Based on analysis of thousands of exam scripts. • Short, snappy explanations focus on key problem areas. • Includes exam-style exercises.